Folate-receptor-targeted co-self-assembly carrier-free gemcitabine nanoparticles loading indocyanine green for chemo-photothermal therapy - Kuang, Shuang; Liu, Shuhan; Wang, Shiyu; Yang, Liang; Zeng, Yingchun; Ming, Xin (Frontiers in Bioengineering and Biotechnology, 2023)
The carrier-free chemo-photothermal therapy has become a promising strategy to improve anticancer therapeutic efficacy owing to the combination of chemotherapy and photothermal therapy, with improved chemotherapy drug pharmacodynamics and pharmacokinetics, high drug loading, and reduced toxicity. We designed a novel carrier-free targeting nanoparticles, co-self-assembled amphiphilic prodrugs 3',5'-dioleoyl gemcitabine (DOG) and tumor-targeted γ-octadecyl folate (MOFA), with encapsulated US Food and Drug Administration (FDA)-approved photosensitizer indocyanine green (ICG) for synergistic chemo-photothermal therapy. The DOG linking oleic acid to the sugar moiety of gemcitabine (GEM) showed better self-assembly ability among GEM amphiphilic prodrugs linking different fatty acids. The readily available and highly reproducible 3',5'dioleoyl gemcitabine/γ-octadecyl folate/indocyanine green (DOG/MOFA/ICG) nanoparticles were prepared by reprecipitation and showed nano-scale structure with mono-dispersity, great encapsulation efficiency of ICG (approximately 74%), acid-and laser irradiation-triggered GEM release in vitro and sustained GEM release in vivo after intravenous administration as well as excellent temperature conversion (57.0°C) with near-infrared laser irradiation. The combinational DOG/MOFA/ICG nanoparticles with near-infrared laser irradiation showed better anti-tumor efficacy than individual chemotherapy or photothermal therapy, with very low hemolysis and inappreciable toxicity for L929 cells. This co-self-assembly of the ICG and the chemotherapy drug (GEM) provides a novel tactic for rational design of multifunctional nanosystems for targeting drug delivery and theranostics.